Internal and external employability of employees: a study among employees in Klang Valley, Malaysia - Juhdi, Nurita; Pa'wan, Fatimah; Othman, Noor Akmar; Moksin, Hanifah (2010)
The paper aimed at examining factors that influence employees’ employability. Factors that were examined are training supports, interpersonal relationship, amount of training given, the level of job experiences, education level and tenure with current job. Employability is measured using two dimensions; internal and external employability. Pearson correlation tests indicated that training support was positively related to external employability (r = 0.193, p = .001) and internal employability (r = 0.182, p = .002). Interpersonal relationship was found only significantly related to external employability (r = 0.125, p = .022).The relationship with internal employability was insignificant (r = 0.100, p = .054). Amount of training received by employees were both related to internal (r = .251, p= .000) and external employability (r = .167, p = .003). On the other hand, job experiences was only significantly related to internal employability (r =.219, p = .000). Education level and tenure were found only giving significant influence to external employability.